2015
DOI: 10.1245/s10434-015-4481-8
|View full text |Cite
|
Sign up to set email alerts
|

The Preoperative Lymphocyte-to-Monocyte Ratio is Prognostic of Clinical Outcomes for Patients with Liver-Only Colorectal Metastases in the Neoadjuvant Setting

Abstract: This study identified preoperative LMR as an independent prognostic factor for PRS, CSS, and OS but not for DFS in patients undergoing hepatectomy for liver-only colorectal metastases. In the future, interventions to augment immune function could improve survival for low-LMR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 26 publications
2
38
1
1
Order By: Relevance
“…The association between LMR and OS was reported in 44 studies enrolling 14,984 patients with various cancer types [8, 1013, 1517, 1921, 2327, 2933, 3540, 4246, 48, 49, 51, 53–56, 5862]. Five of the eligible 44 studies (11%) reported a non-statistically significant hazard ratio.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The association between LMR and OS was reported in 44 studies enrolling 14,984 patients with various cancer types [8, 1013, 1517, 1921, 2327, 2933, 3540, 4246, 48, 49, 51, 53–56, 5862]. Five of the eligible 44 studies (11%) reported a non-statistically significant hazard ratio.…”
Section: Resultsmentioning
confidence: 98%
“…Eleven studies comprising 3,972 patients reported hazard ratios for CSS [7, 8, 11, 18, 19, 22, 24, 25, 44, 58, 59]. The effect of LMR on CSS among cancer subgroups is presented in Figure 4A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NLR has been reported to be an independent factor of clinical outcomes in coronary artery disease, and an attractive biomarker for predicting the severity of the lesion, which has potential to be a universal biomarker in clinical applications [1720]. MLR has been proved to be a prognostic factor in patients with malignancies and tuberculosis [2124]. However, the role of MLR in CAD is still unknown.…”
Section: Introductionmentioning
confidence: 99%